Determinants of long-term unemployment in early adulthood: A Finnish birth cohort study. (August 2019) - Lallukka, Tea; Kerkelä, Martta; Ristikari, Tiina; Merikukka, Marko; Hiilamo, Heikki; Virtanen, Marianna; Øverland, Simon; Gissler, Mika; Halonen, Jaana I.
Abstract: Cumulative contributions of social and health-related determinants to long-term unemployment during early working life among young adults are poorly understood. Therefore, we used four cumulative indices of both parental and own social and health-related determinants of such unemployment among a cohort which comprised a complete census of children born in Finland in 1987. The cohort participants were registered in the Medical Birth Register, and they were followed-up through 2015 (N = 46 521). We calculated predicted probabilities for long-term unemployment (> 12 months) when participants were 25–28 years. Moreover, we examined whether the associations differed by unemployment at the municipal level. During the follow-up, 4.5% of women and 7.1% of men experienced long-term unemployment. All cumulative indices of parental and own social and health-related determinants predicted the probability of long-term unemployment. The greatest probabilities were observed for own social determinants, both in municipalities with high and low unemployment although the probabilities were higher in the high-unemployment municipalities. Of the individual determinants, poor school performance showed the strongest association with long-term unemployment among women (OR 6.65, 95% CI 5.21–8.55) and men (OR 3.70, 95% CI 2.96–4.67), after adjusting for other own social determinants. The results highlight the importance of life course social equality in the prevention of long-term unemployment in early adulthood. Highlights: Parental and own social and health-related factors predict long-term unemployment. Particularly poor school performance increases the odds for long-term unemployment. With high municipal unemployment rates, effects of social disadvantage are emphasized. Those better off have a lower risk of unemployment even in high unemployment areas.